Early diagnosis of acute rheumatic fever and rheumatic heart disease as part of a secondary prevention strategy: Narrative review. (23rd July 2021) - Bennett, Julie; Rentta, Neilenuo N; Leung, William; Atkinson, June; Wilson, Nigel; Webb, Rachel; Baker, Michael G
Abstract : Acute rheumatic fever (ARF) and its sequela rheumatic heart disease (RHD) remain significant causes of morbidity and mortality. In New Zealand, ARF almost exclusively affects Indigenous Māori and Pacific children. This narrative review aims to present secondary interventions to improve early and accurate diagnosis of ARF and RHD, in order to minimise disease progression in New Zealand. Medline, EMBASE and Scopus databases were searched as well as other electronic publications. Included were 56 publications from 1980 onwards. Diagnosing ARF and RHD as early as possible is central to reducing disease progression. Recent identification of specific ARF biomarkers offer the opportunity to aid initial diagnosis and portable echocardiography has the potential to detect undiagnosed RHD in high‐risk areas. However, further research into the benefits and risks to children with subclinical RHD is necessary, as well as an economic evaluation.